The return of the real the avant-garde at the end of the century - Foster, Hal (The MIT Press, 1996)
The Return of the Real presents an original reading of art and theory over the last three decades, with special emphasis to the controversial connections between the two. It also rethinks the relation between historical avant gardes and neo-avant-gardes. The result is an authoritative genealogy of art and theory from minimalism and pop to the present, with important ramifications for prewar studies as well. Against the cliche that contemporary art and theory are condemned to historical pastiche, Foster argues that the avant-garde returns to us from the future, repositioned by innovative work in the present. And he poses this retroactive model of art and theory against the reactionary undoing of progressive culture that is so pervasive today.